Membedah Diskursus dan Berkreasi dalam Ranah Pluralitas: Rereading Arkeologi Pengetahuan - Sanusi, Irfan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
<!–[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 11.0pt; font-family: 'Bookman Old Style','serif'; mso-fareast-font-family: 'Times New Roman'; letter-spacing: -.5pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Archaeology tries to define not the thoughts, representations, images, themes, preoccupations that are concealed or revealed in discourses; but those discourses themselves, those discourses as practices obeying certain rules. <span style="font-size: 11.0pt; font-family: 'Bookman Old Style','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; letter-spacing: -.5pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> (Michel Foucault)<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><div style="mso-element: frame; mso-element-frame-hspace: 9.0pt; mso-element-wrap: around; mso-element-anchor-vertical: page; mso-element-anchor-horizontal: margin; mso-element-top: 224.3pt; mso-height-rule: exactly;"> <p style="margin: 0cm; margin-bottom: .0001pt; text-align: justify; mso-element: frame; mso-element-frame-hspace: 9.0pt; mso-element-wrap: around; mso-element-anchor-vertical: page; mso-element-anchor-horizontal: margin; mso-element-top: 224.3pt; mso-height-rule: exactly;">Archaeology tries to define not the thoughts, representations, images, themes, preoccupations that are concealed or revealed in discourses; but those discourses themselves, those discourses as practices obeying certain rules. (Michel Foucault) <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>